Comparative shotgun metagenomic data of the silkworm Bombyx mori gut microbiome - Chen, Bosheng (Sci Data, 2018)
Lepidoptera (butterflies and moths) is a major insect order including important pollinators and agricultural pests, however their microbiomes are little studied. Here, using next-generation sequencing (NGS)-based shotgun metagenomics, we characterize both the biodiversity and functional potential of gut microbiota of a lepidopteran model insect, the silkworm Bombyx mori. Two metagenomes, including the standard inbred strain Dazao (P50) and an improved hybrid strain Qiufeng × Baiyu (QB) widely used in commercial silk production, were generated, containing 45,505,084 and 69,127,002 raw reads, respectively. Taxonomic analysis revealed that a total of 663 bacterial species were identified in P50 silkworms, while 322 unique species in QB silkworms. Notably, Enterobacter, Acinetobacter and Enterococcus were dominated in both strains. The further functional annotation was performed by both BlastP and MG-RAST against various databases including Nr, COG, KEGG, CAZy and SignalP, which revealed >5 × 10(6) protein-coding genes. These datasets not only provide first insights into all bacterial genes in silkworm guts, but also help to generate hypotheses for subsequently testing functional traits of gut microbiota in an important insect group.